Between Justice and Hidden Intent: Proving Hate Crimes in Comparative Law - Abdelaziz, Dalia Kadry Ahmed (Journal of Ecohumanism, 2025)
To compare law insight to the dimension of hidden intent in a hate crime. Therefore, if one is to consider a crime to be a hate crime, showing the intent of hatred is a fundamental part of this process. The study examines the proofs and legal challenges in establishing such intent, especially in the case of defendants whose misdeeds were previously referenced as using circumstantial evidence, like behaviors, racist discourse, and symbols of hatred. It further looks into the ethical and political influences on judicial processes, investigating how media, public opinion, and hate speech impact the reading of evidence. The study explores the comparison of the legal systems of the United States with those of the United Kingdom, France, and Germany. It ends by providing legal recommendations to improve mechanisms for demonstrating latent intent and guaranteeing the right to a fair trial in hate crime cases.